2008
DOI: 10.1021/jf072475g
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Oxidation in Ready-to-Eat Infant Foods During Storage

Abstract: The effect of storage on sterol oxidation of ready-to-eat infant foods was evaluated. Two different liquid infant foods (honey or fruits flavors), prepared with milk and cereals, were stored for 0, 2, 4, 7 and 9 months at 25°C. Sterol oxidation products (SOP) were isolated by cold saponification, purified by silica solid-phase extraction, and analyzed by gas chromatography (GC) and GC-mass spectrometry. -Sitosterol was the most representative sterol, followed by cholesterol and campesterol. No significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 35 publications
3
21
1
Order By: Relevance
“…In milk-based infant foods, the extent of stigmasterol oxidation (2.9%) was higher than that of cholesterol (1.9%) and -sitosterol (1.4%) (49). In our work, the oxidation percentages obtained for each type of sterol (oxysterols/sterols × 100) ( Table 4) showed that -sitosterol and stigmasterol were the compounds least affected by the oxidation process, cholesterol being the one with the highest oxidation percentages in every sample.…”
Section: Resultsmentioning
confidence: 89%
“…In milk-based infant foods, the extent of stigmasterol oxidation (2.9%) was higher than that of cholesterol (1.9%) and -sitosterol (1.4%) (49). In our work, the oxidation percentages obtained for each type of sterol (oxysterols/sterols × 100) ( Table 4) showed that -sitosterol and stigmasterol were the compounds least affected by the oxidation process, cholesterol being the one with the highest oxidation percentages in every sample.…”
Section: Resultsmentioning
confidence: 89%
“…In another study by our group, POP contents from β-sitosterol, stigmasterol and campesterol were determined in milk and cereal based infant foods (García-Llatas et al, 2008), resulting in 7-ketoderivatives of β-sitosterol > stigmasterol > campesterol. The total POP contents were low (0.9-16.1 μg of POPs/100 g of sample), though these foodstuffs were not enriched with PS.…”
Section: Determination Of Phytosterol Oxidation Productsmentioning
confidence: 99%
“…However, few studies to date have identified and quantified POPs in other foods, and the existing publications mostly focus on high lipid content matrixes (Bortolomeazzi, Cordano, Pizzale, & Conte, 2003;Dutta, 2002;Soupas, Huikko, Lampi, & Piironen, 2007). In the case of dairy matrixes, 7-ketositosterol contents have been determined as an indicator of phytosterol oxidation in milk-based infant foods (Zunin, Calcagno, & Evangelisti, 1998), and several POPs have been quantified in milk-and cereal-based infant foods (García-Llatas et al, 2008). Plant sterol stability in enriched dairy products was determined for the first time by Soupas et al (2006), who reported POP contents in skimmed milk enriched with free or esterified PS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies were conducted on the analysis of foods added with PS such as spread, milk, yogurt drink, milkbased fruit beverage and fruit beverage [25][26][27][28]42]. These food items are relatively simple products that are consumed as such without further cooking being involved.…”
Section: Tablementioning
confidence: 99%
“…Both GC with flame ionization detection (GC-FID) as well as GC-mass spectrometry (GC-MS) have been widely used [13,23,24]. Several studies have been conducted on the analysis of the sterol content by GC in foods with added PS such as spread, milk, yogurt drink, milk-based fruit beverage and fruit beverage [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%